2018
DOI: 10.1111/jan.13707
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of forced air warming during sedation in the cardiac catheterisation laboratory

Abstract: Forced air warming could be considered cost-effective for procedures performed with sedation in a cardiac catheterisation laboratory if the extra cost of an incremental gain in thermal comfort is less than the decision maker's willingness to pay for it. Therefore, those responsible for decision-making regarding use of FAW in the cardiac catheterisation laboratory can use results of our model to decide if it represents good value for their organisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Studies investigating the effect of heating on thermal comfort in the preoperative, intraoperative, and postoperative periods (12,24,29), in both preoperative and intraoperative periods and intraoperative periods (30,31) have determined that heating increases thermal comfort. Another study has demonstrated that heating with gowns blowing warm air increases the thermal comfort level in patients undergoing cardiac catheterization under sedation (32). This study is similar to the findings in the literature that active heating increases thermal comfort.…”
Section: Thermal Comfort Levelsupporting
confidence: 88%
“…Studies investigating the effect of heating on thermal comfort in the preoperative, intraoperative, and postoperative periods (12,24,29), in both preoperative and intraoperative periods and intraoperative periods (30,31) have determined that heating increases thermal comfort. Another study has demonstrated that heating with gowns blowing warm air increases the thermal comfort level in patients undergoing cardiac catheterization under sedation (32). This study is similar to the findings in the literature that active heating increases thermal comfort.…”
Section: Thermal Comfort Levelsupporting
confidence: 88%
“…It is also important to note that analgo-sedation can redistribute blood volume towards the body's periphery, thereby lowering core temperature. While involving some additional costs [19], forced air warming during cardiac catheterization is advisable, at least prior to and after the procedure (paused during the intervention given the potential interference with electrocardiogram monitoring) [20].…”
Section: General Considerationsmentioning
confidence: 99%